2014
DOI: 10.1002/rra.2818
|View full text |Cite
|
Sign up to set email alerts
|

Diatoms of Temporary and Permanent Watercourses in Southern Europe (Portugal)

Abstract: The potential importance of benthic diatoms in Mediterranean watercourses has received limited academic attention historically. This study sought to provide baseline information for this poorly studied group. Temporary and permanent watercourses in Portugal differ in catchment characteristics, climatic variables and water chemistry. The benthic diatom communities were characterized in terms of ecological preferences and conservation status for taxa with relative abundance above 1% in at least one site covering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 36 publications
4
32
0
Order By: Relevance
“…The species seems to be rarer and even occasional (e.g. Blanco et al 2008, Barinova & Tavassi 2009, Falasco & Bona 2011, Novais et al 2014) compared to P. lanceolatum; it can reach higher abundances in Russia (Kulikovskiy et al 2010, Hoff et al 2014 and North America (i.e. Lowe & Cody 2002).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The species seems to be rarer and even occasional (e.g. Blanco et al 2008, Barinova & Tavassi 2009, Falasco & Bona 2011, Novais et al 2014) compared to P. lanceolatum; it can reach higher abundances in Russia (Kulikovskiy et al 2010, Hoff et al 2014 and North America (i.e. Lowe & Cody 2002).…”
Section: Resultsmentioning
confidence: 97%
“…6) including: -Paleartic (i.e. Terry 1908, Meister 1912, Kaiser 1916, Steinecke 1916, Héribaud 1920, Cholnoky 1922, Rich 1925, Budde 1929, Szemes 1931, 1960, Bastow 1949, Topachevsky & Oksiyuk 1960, Robinson 1982, Hartley 1986, Lange-Bertalot & Krammer 1989, Wendker 1990, Pastor 1991, Medvedeva 1994, Müllner 1995, Laugaste & Pork 1996, Temniskova-Topalova & Ognjanova-Rumenova 1997, Bukhtiyarova 1999, Lange-Bertalot & Genkal 1999, Balbi 2000, Nikulina 2001, 2006, 2010a, 2010b, 2014, Pierre 2001, Kawecka 2003, Karayeva & Dzhafarova 2004, Medvedeva & Barinova 2004, Barinova et al 2005, Korol 2005, Novoveska 2005, Reiter & Burchardt 2005, Savateev & Medvedeva 2005, Shevchenko 2007, Blanco et al 2008…”
Section: Resultsmentioning
confidence: 99%
“…Barthès et al (2014) observed a significant and long-lasting impact of even short-term drought events on diatom assemblage structure. On the contrary, Novais et al (2014) found that diatom richness increased with flow intermittency.…”
Section: Biotic Responses To Flow Intermittencymentioning
confidence: 89%
“…Recent research has led to a better inventory and understanding of biotic assemblages in NPRS, including aquatic (Graça et al, 2004;Datry, 2012;Bonada and Resh, 2013;García-Roger et al, 2013) and terrestrial invertebrates Datry, 2012, 2015;, diatoms (Novais et al, 2014;Barthès et al, 2014), microbial and algal assemblages (Amalfitano et al, 2008;Romani et al, 2013) as well as vertebrate assemblages, such as fish (Pires et al, 1999;Zogaris et al, 2012;Vardakas et al, 2015) and semi-aquatic carnivores (Clavero et al, 2003;Ruiz-Olmo et al, 2002. Other recent studies focused on the mechanisms allowing species to cope with recurrent drying as well as to produce quantitative relationships between drying duration and frequency (Datry et al, 2014b).…”
Section: Biotic Responses To Flow Intermittencymentioning
confidence: 99%
“…Their use as indicators is currently limited when assessing water quality as required under the European Water Framework Directive (WFD, Directive /60/EC, 2000). Diatom taxon richness is higher in temporary Mediterranean watercourses than in permanently flowing systems, providing a strong rationale for further research to assess their utility as biological indicators and support the conservation of biodiversity in headwater streams in particular (Novais et al ., in press).…”
Section: Synthesis Of Papersmentioning
confidence: 99%